ANALISIS KESALAHAN KAIDAH EJAAN BAHASA INDONESIA (EBI) DALAM ARTIKEL KESEHATAN DAN ARTIKEL HIBURAN RADAR MOJOKERTO EDISI BULAN JANUARI-FEBRUARI 2018 SERTA RELEVANSINYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA - Indria Devi Andini (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
This study aims to describe: (1) Error writing letters (2) Wrong writing, (3) misuse of punctuation, (4) writing errors of absorption elements, (5) Relevance of EBI in Indonesian Language Learning in Senior High Schools.The method used in this study is a descriptive qualitative method with a discourse analysis approach. The subjects used in this study were written data or literature, namely in the form of Mojokerto Newspaper Articles. The object of this study is in the form of text on Radar Mojokerto Articles in the study of Language Errors. Data collection techniques use observation, interview, and documentation techniques. Researchers play the role of using reading, notes and literature study techniques. Validation of the data was obtained through triangulation of data sources, methods, and theories. Data analysis used was the interactive analysis model by collecting data, reducing data, displaying data, and verifying data. The results obtained from the study showed that: (1) Errors in letter writing in health articles and entertainment articles of Radar Mojokerto in total amounted to 16 data, including misuse of italics and incorrect use of bold letters (2) Error writing words in health articles and entertainment articles Radar Mojokerto in total amounted to 4 data which included writing errors in front and particle words, (3) misuse of punctuation in health articles and Radar Mojokerto entertainment articles in total totaling 5 data which included the use of punctuation points (.), comma (,) punctuation marks and hyphens (-), (4) writing errors of absorption elements in health articles and Radar Mojokerto entertainment articles in total totaling 2 which include writing errors of positive word absorption elements and ornament, (5) EBI relevance in learning Indonesian in high school in accordance with KI 4, KD 3.1. Keyword : EBI (Indonesian spelling), Spelling errors, relevance of language learning